Policy Challenges for Education and Economic Growth in the Slovak Republic - World Bank (Washington, DC, 2014)
This policy note examines this question as to whether Slovakia's education system will play a strong supporting role in maintaining the impressive record in economic growth. It begins by describing several features of the education system that constitute a potential threat to continued economic growth. Next it identifies some of the factors contributing to suboptimal education performance. It concludes with a number of reform options for policy actions to ensure that education plays a positive role in supporting strong economic growth in the future.